TOLERANCE CHARACTER BUILDING THROUGH MARSIALAPARI TRADITION: A Case Study of Huta Padang Village Community, Mandailing Natal - Rohman, Rohman Rohman; Irma Suryani Siregar (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2024)
This research aims to explore the application of the marsialapari tradition in Huta Padang Village, Mandailing Natal, and its impact on the character building of tolerance in the local community. The tradition of marsialapari, a typical practice of gotong royong in Mandailing and Angkola culture, continues to be preserved in this village even though the influence of modernization has eroded it in many other places. This type of research is qualitative with a case study approach. Data were collected through in-depth interviews, participatory observation, and document analysis. The results show that marsialapari not only plays a role in supporting agricultural activities, but also as an important mechanism in building and maintaining tolerance values among people of diverse religions. Through participation in this tradition, the people of Huta Padang Village develop mutual respect, openness and empathy, which characterize tolerant characters. This finding is reinforced by functionalism theory, which highlights the role of tradition in maintaining social stability, and social capital theory, which emphasizes the importance of consistent social interaction in strengthening social cohesion. Thus, this study reveals that marsialapari is not just a cultural heritage, but also a strategic tool to maintain social harmony in a multicultural society.